Biosensors: Large‐Scale Parallel Surface Functionalization of Goblet‐type Whispering Gallery Mode Microcavity Arrays for Biosensing Applications (Small 19/2014). Issue 19 (October 2014) - Bog, Uwe; Brinkmann, Falko; Kalt, Heinz; Koos, Christian; Mappes, Timo; Hirtz, Michael; Fuchs, Harald; Köber, Sebastian
<x xml:space="preserve">Abstract</x> To enable competitive biomolecular screening of complex analytes, dense and selective surface functionalization of sensor transducers is imperative. On page 3863, M. Hirtz, S. Koeber, and co‐workers report a novel technique allowing the large‐scale deposition of functional inks onto individual chip‐based sensors. Polymer pen lithography‐prepared glass slides act as custom stamp pads to directly print biochemical acceptor molecules. The technique is applied to densely packaged arrays of whispering gallery mode microgoblet cavities, which are then shown to function as biosensors. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>